Analisis Kausalitas Pengeluaran Militer dan Pertumbuhan Ekonomi di Negara ASEAN-5 : Analisis Kausalitas Pengeluaran Militer dan Pertumbuhan Ekonomi di Negara ASEAN-5 - Ibon, Naifah Dwina; Irfan, Muhammad (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to analyze the causal relationship between military spending and economic growth in ASEAN-5 countries. This study uses panel data from 1980-2022 from World Bank and Stockholm International Peace Research Institute (SIPRI) publication data. The data analysis used is descriptive analysis and inductive analysis. The analysis method used is the Vector Autoregression (VAR) model which is continued with the Panel Vector Error Correction Model (PVECM) model and the Panel Granger Causality Test. In addition, the cointegration test used in this study was carried out using the Johansen Cointegration Test. The results of this study indicate that: There is no causal relationship between military spending and economic growth in ASEAN-5 countries. Military spending does not significantly affect economic growth in ASEAN-5 countries in 1980-2022. However, there is a unidirectional relationship between economic growth and military spending. Economic growth significantly affects military spending. There is a long-term and short-term relationship between military spending and economic growth that has a negative effect.